1988
DOI: 10.1111/j.1432-1033.1988.tb14065.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a myometrial oxytocin‐receptor protein

Abstract: The specific binding of [3H]oxytoxin to uterine membrane peparations derived from different species at late pregnancy was examined. The highest receptor density (b,,, value) was found in membranes derived from the myometria of guinea pigs between day 60 post-conception (b,,, = 3.6 f 0.1 pmol/mg) and day 65 (b,,, = 4.4 f 0.1 pmol/mg). The similarity of & values for oxytocin binding (Kd = 2.6 f 0.2 nM) and for vasopressin binding (& = 2.1 f 0.4 nM) to the same membranes derived from a guinea pig myometrium indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The absolute values for B max in the present study are similar to those reported by Chwalisz et al [29] and Fuchs et al [17], fourfold lower than those published by Fahrenholz et al [18], and 25 times higher than those obtained by one-point determinations [16]. Values of Hill coefficients close to unity, as assessed in our experiments, are similar to published values of 1.1-1.8 at 60-65 days of gestation [18,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The absolute values for B max in the present study are similar to those reported by Chwalisz et al [29] and Fuchs et al [17], fourfold lower than those published by Fahrenholz et al [18], and 25 times higher than those obtained by one-point determinations [16]. Values of Hill coefficients close to unity, as assessed in our experiments, are similar to published values of 1.1-1.8 at 60-65 days of gestation [18,29].…”
Section: Discussionsupporting
confidence: 92%
“…As the dissociation constant (K d ) of myometrial oxytocin receptors was not determined in that study [16], the biological significance of these findings remains uncertain. Dissociation constants of 1.9 ϫ 10 Ϫ9 M [17] and of 6.9 Ϯ 0.3 ϫ 10 Ϫ9 M [18] at 60 days of gestation and of 2.6 Ϯ 0.2 x 10 Ϫ9 M at 65 days [18] were reported in later studies in which binding of oxytocin was studied over a limited range of oxytocin concentrations (10 Ϫ10 to 10 Ϫ7 M). This range did not permit the investigators to determine whether binding sites with K d s Ͼ 10 Ϫ8 M exist.…”
Section: Introductionmentioning
confidence: 95%
“…Myometrial plasma membranes were prepared from myometrial tissue from pregnant guinea pigs on day 50 of gestation by modifications of the method used for preparation of rat myometrial membranes (Alexandrova and Soloff, 1980), as described (Fahrenholz et al, 1988), and stored frozen at -70°C.…”
Section: Membrane Preparation and Receptor Binding Assaymentioning
confidence: 99%
“…Protein chemical studies, especially photoaffinity labeling experiments and enzymic deglycosylation of the myometrial oxytocin receptor from guinea pig, showed that the oxytocin receptor is highly glycosylated, with an apparent molecular mass between 68-80kDa (Kojro et al, 1991). At present, the functional domains of the receptor protein responsible for hormone binding and coupling with G-proteins are unknown, mainly because the purification of the receptor protein has not been achieved.Guinea pig uterus is the tissue of choice for purification of the myometrial oxytocin receptor because of its high receptor density at late pregnancy (Fahrenholz et al, 1988). In contrast to the solubilization of the oxytocin receptor from rat mammary gland (Soloff and Fernstrom, 1987), it has so far not been possible to achieve solubilization of the oxytocin receptor from guinea pig uterus without losing its binding activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation